Eastern extension of European union: restraint or chance for Muslim world? - Rosel, Jackob (2002)
With the eastern wave of accession the European Union has now reached a critical mass and an important threshold where further widening might well endanger institutional integration. This new wave of accession will have significant consequences for the Muslim world and in general repercussions on the third world countries. - Reproduced.
Keywords: European Union